A single‐phase earth fault location scheme for distribution feeder on the basis of the difference of zero mode traveling waves. (1st December 2016) - Zhou, Cong‐Cong; Shu, Qin; Han, Xiao‐Yan
Summary: To eliminate the effect of line structure and unbalanced loads on the location of single‐phase earth fault in distribution network, a new fault location method is proposed. In this method, the difference of the 2 zero mode traveling waves is taken as the criterion via injecting high voltage pulses into fault phase and nonfault phase, respectively. Through analyzing the transient response characteristic of distribution transformer and the propagation equation of traveling wave at the fault point, it is theoretically proved that the first difference of the 2 zero mode traveling waves is rooted in the reflection of the twice different incident wave of aerial mode voltage at the fault point, and further the fault location formula is obtained. The PSCAD‐based simulation results show that the proposed method is effective and accurate to estimate fault distance. Also it has an excellent precision within certain extent.